The International Financial Society Limited [electronic resource] : issue of stock in the Hudson's Bay Company, incorporated by royal charter, 1670 : prospectus. - International Financial Society. ([S.l. : s.n., 1863)
Electronic reproduction. Mode of access: Internet. 44